Development of Single Nucleotide Polymorphism and Phylogenetic Analysis of Rhododendron Species in Zhejiang Province, China, Using ddRAD-Seq Technology - Hong Zhu; Dongbin Li; Chunlei Yue; Hepeng Li (Plants)
The genus Rhododendron presents significant challenges for systematic classification due to extensive hybridization and adaptive radiation. Here, we employed double-digest restriction site-associated DNA sequencing (ddRAD-seq) to resolve phylogenetic relationships among nine ecologically significant Rhododendron species (34 accessions) endemic to Zhejiang Province, China, a biodiversity hotspot for this genus. Using R. simsii as the reference genome, we generated 39.40 Gb of high-quality sequencing data with a Q30 score of 96.65% and a GC content of 39.63%, achieving an average alignment rate of 92.79%. Through stringent filtering (QD ≥ 2, MQ ≥ 40), we identified 14,048,702 genome-wide single nucleotide polymorphism (SNP), predominantly characterized by the mutation types T:A>C:G and C:G>T:A. The widespread R. simsii and R. simsii var. putuoense exhibited significant genetic diversity, whereas the low-altitude widespread R. molle and the endemic R. simiarum exhibited lower genetic diversity. Moderate genetic differentiation (Fst = 0.097) was observed between R. simsii and R. simsii var. putuoense, while substantial genetic differentiation was detected among the other Rhododendron species. Principal component analysis (PCA), combined with phylogenomic reconstruction, demonstrated that the Rhododendron genus can be stratified into six well-supported genetic clades. Furthermore, this study provides the first genomic validation of the sibling relationship between R. simsii and its variety, R. simsii var. putuoense, and clarifies the systematic position of R. huadingense, suggesting that it should be classified as a new subgenus. This study establishes ddRAD-seq as a cost-effective tool, providing both a theoretical framework for SNP-based phylogenetics and critical insights for conserving China’s azalea biodiversity.